Analisa Penentuan Jurusan Siswa Baru Dengan Metode Simple Multi Attribute Rating Technique (SMART) - Satria; Hs. Sulistiyowati .; Andrean Budi Setyanto; Widiyawati . (Jurnal ICT: Information Communication & Technology, 2023)
SMK Al Muhadjirin 2 Bekasi is one of the schools with a major in the health sector, namely Clinical Pharmacy and Nursing Assistant. The decision to determine the school's major must be correct, and the determination of this major starts from the beginning of registration by taking several tests, so that the decision is not wrong towards students. The problem that often occurs in the process of majoring is the emergence of the same high grades in each of the pharmacy and nursing departments, or the appearance of the same low grades in those majors. Errors in choosing majors will be detrimental to students, both in terms of cost and time. The decision support system for selecting majors at SMK using the Simple Multi Attribute Rating Technique (SMART) method was built to help schools make it easier to determine majors for students who will enter SMK Al Muhadjirin 2 Bekasi. The criteria to be used are written tests, communications, psychological tests and interviews. The final results of this study will be tested using this method which is able to overcome problems in the process of selecting majors at SMK. Based on 5 samples who received the Nursing Assistant major with a score of <= 22, namely Alfi Zahra, Devita and Zahra Kirana. Department of Clinical Pharmacy with grades >= 23, namely Hirdi Editra and Muhammad Fitri.